(3TQM GdYbjOI GdGUagGfjIs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s; (3GdCUagGfj , CHh YHO Gddg,J (B688 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI SFd TjN GdESdGe Hf JjejI GdMQGe hgh ebje HGdOjGQ GdeUQjI aj TghQ SfI GKfj YTQ hSHYeGFI Cf CTQM YbjOI eNJUQI CdagG GdTjN TeS GdOjf GdGUagGfj s
(3BNQgG (B:s
(3hdgPG de fYRa gPG Gdbhd Yf GMO ef Sda GdCeI hCFeJgG GdCQHYI hdG ZjQge , Hd bO PcQ CHh fUQ GdSLRj hCHh GdbGSe SYO Hf Ydi GdRfLGfj hZjQgG ef Cgd GdMOjK s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B87 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B6s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs